Effect of moisture content and microwave power on puffed yield and expansion volume of Malaysian paddy variety MR297 - Abdul Rahman H.,; Salleh M.H.M.,; Md Salim N.S., (Penerbit Universiti Kebangsaan Malaysia, 2019)
Puffed rice, is a popular ready-to-eat product especially in South-East Asia. In this study, an attempt is made to examine the effectiveness of puffing the Malaysia paddy variety MR297 using domestic microwave oven. The experiment was carried out based on two parameters, which are three levels of microwave power (600, 700 and 800 Watt) and three levels of moisture content (11, 14 and 17 % w.b.). The best condition for puffing the paddy was determined based on the puffed yield and expansion volume. The results show that adequate moisture content is required to generate sufficient internal pressure for puffing. The puffed yield and expansion volume were higher with an increase in microwave power. The best conditions to obtain highest puffing yield with the expansion volume of 2.22 mL/g were found to be at a moisture content of 14% w.b. with the microwave power level of 800 Watt. Further studies need to be carried out in order to improve the performance of microwave puffing process for Malaysia paddy variety MR297.